Heart Rate Measurement Accuracy During Intermittent Efforts Under Laboratory Conditions: A Comparative Analysis Between Chest Straps and Armband - Joaquín Martín Marzano-Felisatti; Leonardo De Lucca; José Ignacio Priego-Quesada; José Pino-Ortega (Applied Sciences)
Heart rate (HR) is the most frequently used variable to monitor athletes’ internal load during training and competition. High-intensity effort and abrupt HR changes during exercise have presented measurement accuracy issues depending on the chosen device. Therefore, this study aimed to compare two chest straps (Garmin HRM-Dual and Coospo H6) and one armband (Coospo HW807) during intermittent exercise under controlled laboratory conditions. Thirty active young men performed an indoor cycling protocol consisting of seven intermittent efforts with a 2 min effort stage followed by a 2 min recovery stage. The results show no difference between the chest straps (Garmin vs. Coospo), with a high level of agreement between the two devices (Bias = −0.2 bpm, LoAup = +2.5 bpm, LoAlow = −2.9 bpm, ICC = 0.6–1.0). Differences were found between the chest straps and the armband during effort stages (±5 bpm, p < 0.05), with similar bias and LoA values in the Garmin Strap vs. Coospo Armband (Bias = −0.5 bpm, LoAup = 8.3 bpm, LoAlow = −9.3 bpm) and Coospo Strap vs. Coospo Armband (Bias = −0.4 bpm, LoAup = 8.3 bpm, LoAlow = −9.0 bpm) comparison. Chest straps (Garmin HRM-Dual and Coospo H6) accurately measure HR during intermittent exercise with abrupt HR changes. However, caution should be taken when using armbands (Coospo HW807) to monitor intermittent and high-intensity effort.